IMPLEMENTATION OF ENTREPRENEURSHIP COURSES IN INCREASING STUDENTS' INTEREST IN ENTREPRENEURS - Sugiyanto Sugiyanto; Makhda Intan Sanusi (SEAN Institute, 2023)
This article aims to describe the impact of entrepreneurship courses on increasing students' interest in developing businesses. This research uses a qualitative descriptive research type. Data was collected through observation, in-depth interviews and documentation. Data collection techniques in this research include observation and in-depth interviews. The results of this research include that students are starting to understand what entrepreneurship is well. So far they have been afraid of entrepreneurship because they don't know or don't understand entrepreneurship itself. By studying entrepreneurship courses they have good knowledge and knowledge, increasing their interest in becoming an entrepreneur. After understanding entrepreneurship well, they are interested in becoming entrepreneurs because they know the various advantages and benefits of being an entrepreneur and also students think they can create their own business opportunities and the ability to innovate, namely the ability to work and be creative, many students have the skills to create skills after taking part in Entrepreneurship courses, they are enthusiastic about developing their skills and want to sell their work. Some students are motivated to want to take part in training. And there are students who immediately want to try making products.